A numerical solution and evaluation of dynamic stiffness of pile groups and comparison to experimental results. (15th November 2017) - Dai, Wentao; Shi, Chen; Tan, Yong; Rojas, Fabian
Abstract: A number of solutions and computer programs are already available to determine the dynamic stiffness of complete pile foundations, assuming linear elastic soil behavior and perfect bonding between the piles and the surrounding soil. These are assumptions that would be generally valid for properly designed machine foundations where very small strains should be expected. A number of approximate formulations have also been developed. Among these the most commonly used one is that proposed by Poulos (1971) [1, 2] for the static case, computing interaction coefficients between the heads of two piles considered by themselves, then forming a matrix of these coefficients to obtain the interaction between the heads of all the piles in the group. Additional approximations have been suggested, particularly for the computation of the interaction coefficients, using closed form expressions. In this paper, a semi-analytical-semi-numerical formulation has been adopted to calculate the static and dynamic stiffness of pile foundations in the frequency domain, and some approximate expressions are suggested. They are intended for pile groups with pile spacing of the order of two to four diameters, typical range of the modulus of elasticity of the piles over that of the soil between 100 and 1000, and very small amplitude vibrations.